2023
DOI: 10.3390/ijerph20054586
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Trajectory and Risk Factors of Healthcare Workers’ Mental Health during COVID-19 Pandemic: A 24 Month Longitudinal Cohort Study

Abstract: Background: Research has shown the substantial impact of the COVID-19 pandemic on healthcare workers’ (HCWs) mental health, however, it mostly relies on data collected during the early stages of COVID-19. The aim of this study is to assess the long-term trajectory of HCWs’ mental health and the associated risk factors. Methods: a longitudinal cohort study was carried out in an Italian hospital. At Time 1 (July 2020–July 2021), 990 HCWs took part in the study and completed the General Health Questionnaire (GHQ-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 63 publications
0
23
2
Order By: Relevance
“…Previous studies have shown a deterioration in mental health in HCWs early in the pandemic (Sasaki et al, 2021 ). In Australia, a study following HCWs from May 2021 to June 2022 found a deterioration in MH (McGuinness et al, 2023 ) while one from Italy for much the same period found MH improvements (Fattori et al, 2023 ). A systematic review that included 18 longitudinal studies of mental health in HCWs during the pandemic concluded that 12 studies suggested deterioration over time and six improvement, attributing the ‘remarkable variation’ to use of different instruments for measuring MH (Umbetkulova et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown a deterioration in mental health in HCWs early in the pandemic (Sasaki et al, 2021 ). In Australia, a study following HCWs from May 2021 to June 2022 found a deterioration in MH (McGuinness et al, 2023 ) while one from Italy for much the same period found MH improvements (Fattori et al, 2023 ). A systematic review that included 18 longitudinal studies of mental health in HCWs during the pandemic concluded that 12 studies suggested deterioration over time and six improvement, attributing the ‘remarkable variation’ to use of different instruments for measuring MH (Umbetkulova et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a perceived disconnect between societal view of COVID-19 ( e.g. , “postpandemic”) and the lived experience of healthcare workers who may still be caring for patients with coronavirus-related illnesses may itself contribute to moral injury (Fattori et al, 2023; Song et al, 2021). COVID-19 fatigue still exists today, and many employees lost loved ones from the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Although society may have moved on from COVID-19, the results of our data provide utility postpandemic as a potential high-water mark against which interventions against moral injury can be measured. Conversely, a perceived disconnect between societal view of COVID-19 (e.g., "postpandemic") and the lived experience of healthcare workers who may still be caring for patients with coronavirus-related illnesses may itself contribute to moral injury (Fattori et al, 2023;Song et al, 2021). COVID-19 fatigue still exists today, and many employees lost loved ones from the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown a deterioration in mental health in HCWs early in the pandemic [13]. In Australia a study following HCWs from May 2021 to June 2022 found a deterioration in MH [17] while one from Italy for much the same period found MH improvements [18]. A systematic review that included 18 longitudinal studies of mental health in HCWs during the pandemic concluded that 12 studies suggested deterioration over time and 6 improvement, attributing the ‘remarkable variation’ to use of different instruments for measuring MH [10].…”
Section: Discussionmentioning
confidence: 99%